2020
DOI: 10.1021/acsami.0c16953
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Coatings on Polymer Microfibers for Pathogen Inactivation: Effects of Application Method and Composition

Abstract: A substantial increase in the risk of hospital-acquired infections (HAIs) has greatly impacted the global healthcare industry. Harmful pathogens adhere to a variety of surfaces and infect personnel on contact, thereby promoting transmission to new hosts. This is particularly worrisome in the case of antibiotic-resistant pathogens, which constitute a growing threat to human health worldwide and require new preventative routes of disinfection. In this study, we have incorporated different loading levels of a por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
4
24
1
Order By: Relevance
“…While the resultant coating thicknesses varied two-fold across the different materials [PRU (~1.8 μm) > Wolin (~1.4 μm) > Deans (~0.91 μm) > Capri (~0.76 μm)], the thickness of the coating applied to the Husk specimen could not be determined due to the lack of identifiable individual fibers at the highest magnification employed. Compared to our earlier study employing SbQ-PVA/ZnTMPyP 4+ that yielded a coating thickness of ~150-200 nm ( 30 ), here we see a 5-10-fold increase in coating thickness. We attribute the increase here to two factors: (i) a larger quantity of initial SbQ-PVA/ZnTMPyP 4+ solution was used to saturate the thicker Vescom materials compared with the spunbond nylon mats previously employed, resulting in a thicker photoactive base layer; and (ii) the use of two “sealant” coats (achieved by sequential spray and dip coating) on top of the base layer as opposed to a single “sealant” coat (dip only) performed in our previous study.…”
Section: Resultscontrasting
confidence: 89%
See 4 more Smart Citations
“…While the resultant coating thicknesses varied two-fold across the different materials [PRU (~1.8 μm) > Wolin (~1.4 μm) > Deans (~0.91 μm) > Capri (~0.76 μm)], the thickness of the coating applied to the Husk specimen could not be determined due to the lack of identifiable individual fibers at the highest magnification employed. Compared to our earlier study employing SbQ-PVA/ZnTMPyP 4+ that yielded a coating thickness of ~150-200 nm ( 30 ), here we see a 5-10-fold increase in coating thickness. We attribute the increase here to two factors: (i) a larger quantity of initial SbQ-PVA/ZnTMPyP 4+ solution was used to saturate the thicker Vescom materials compared with the spunbond nylon mats previously employed, resulting in a thicker photoactive base layer; and (ii) the use of two “sealant” coats (achieved by sequential spray and dip coating) on top of the base layer as opposed to a single “sealant” coat (dip only) performed in our previous study.…”
Section: Resultscontrasting
confidence: 89%
“…Unless otherwise noted, all in vitro aPDI assays were performed under fixed illumination conditions (60 min, 400-700 nm, 65 ± 5 mW/cm 2 ). These illumination conditions were chosen on the basis of our prior works, and we note that we have previously reported that illumination alone (e.g., light-only control) at the aforementioned intensity and duration is not sufficient to inactivate pathogens without the presence of a PS ( 30 , 43 , 44 ); this was again confirmed here as light-only controls did not show any statistically significant pathogen inactivation ( Supplementary Figure 2 ). As displayed in Figure 6A , neither the SbQ-PVA-only coated materials (PS-free) nor the non-illuminated SbQ-PVA/ZnTMPyP 4+ coated samples (dark controls) exhibited any statistically significant antibacterial activity against methicillin-susceptible S. aureus ATCC-29213, thereby confirming the requirement for both light and addition of PS for photodynamic inactivation of this pathogen (in an oxygen-containing environment).…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations